Methanol distribution and metabolic rate in the northwest Pacific Ocean in May/June 2021 - Zhen Zhou; Guang-Chao Zhuang; Shi-Hai Mao; Jiarui Liu; Xiao-Jun Li; Qiao Liu; Guo-Dong Song; Hong-Hai Zhang; Zhaohui Chen; Andrew Montgomery; Samantha B Joye; Gui-Peng Yang (PANGAEA, 2023)
We investigated the seawater methanol abundance, the dynamic of microbial methanol (MeOH) metabolism and the geochemical parameters in the northwest Pacific Ocean (NWPO) area. Seawater samples were collected during May-June 2021 aboard the R/V “Dongfanghong 3” in the northwest Pacific Ocean. Seawater was sampled using a Seabird 911 CTD-Niskin rosette system equipped with conductivity, temperature and depth sensors. Methanol samples were collected directly without filters and then stored at -80? for laboratory analysis. Methanol concentrations were determined by a modified commercial purge and trap system combined with Agilent GC-8890 gas chromatograph with a flame ionization detector. Microbial methanol assimilation and oxidation rates were determined by quantifying 14C-MeOH incorporation into biomass and oxidation to CO2 (Zhuang et al., 2018). Nutrients were measured using Seal Analytical Quaatro nutrient autoanalyzer except for ammonium which was analyzed by a fluorometric method on board (Ning et al., 2013). Chlorophyll-a was measured by fluorometric method (Parsons et al., 1984).